Nutrient Intake and Nutritional Status of Vegetarians Compared to Non-Vegetarians: A Systematic Literature Review - Sineri, Dessy Ikasartika; Nurwati, Ida; Sumardiyono, S (Universitas Muhammadiyah Surakarta, 2023)
Purpose: A systematic literature review aims to analyze the nutritional intake and nutritional status among adult populations consuming vegetarian and non-vegetarian diets. Methodology: This study employed a systematic literature review (SLR) of journals published from 2013 to 2023. Articles were sourced from the Pubmed, Scopus, and Google Scholar databases. Articles are included if eligible. Results: The research posed specific research questions, and the findings indicated differences in nutrient intake and nutritional status between vegetarian and non-vegetarian populations. The nutritional intake and nutritional status of vegetarians showed better outcomes compared to non-vegetarians. However, dietary adjustments are necessary to ensure nutritional adequacy. Applications/Originality/Value: A systematic literature review contributes to comparing nutrient intake and nutritional status vegetarians and non-vegetarians. Systematic literature review of this study compares several articles with different research objects, research samples, methods and results.